2020
DOI: 10.1101/2020.05.27.20114298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased expression of ACE2, the SARS-CoV-2 entry receptor, in alveolar and bronchial epithelium of smokers and COPD subjects

Abstract: Rationale: Smokers and patients with chronic obstructive pulmonary disease (COPD) are at increased risk for severe Coronavirus Disease 2019 (COVID-19). Objectives: We investigated the expression of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) entry receptor ACE2 and the protease TMPRSS2 in lung tissue from never smokers and smokers with and without COPD. Methods: In a cross-sectional, observational study we measured mRNA expression of ACE2 and TMPRSS2 by RT-PCR in lung tissue samples from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
2
11
0
1
Order By: Relevance
“…SARS-CoV-2 achieves host cell entry primarily via membrane-bound ACE2. We previously showed that ACE2 gene and protein expression was increased in the bronchial epithelium (6) and lung tissue (7) of people with COPD, a finding confirmed by other investigators (27, 28). Increased availability of ACE2 may increase the susceptibility to infection and the risk of severe COVID-19 (29, 30).…”
Section: Discussionsupporting
confidence: 79%
“…SARS-CoV-2 achieves host cell entry primarily via membrane-bound ACE2. We previously showed that ACE2 gene and protein expression was increased in the bronchial epithelium (6) and lung tissue (7) of people with COPD, a finding confirmed by other investigators (27, 28). Increased availability of ACE2 may increase the susceptibility to infection and the risk of severe COVID-19 (29, 30).…”
Section: Discussionsupporting
confidence: 79%
“…Among published studies, there is an overrepresentation of analyses of RNA datasets from lungs of smokers compared to nonsmokers or from resident lung cells. Findings from these studies have been variable with most showing persuasive evidence of ACE2 induction among smokers while others show no significant difference (25)(26)(27)(28)(29)(30)(31). Further, the few studies that examined ACE2 protein expression in the lungs or in the resident cells of smokers versus nonsmokers have been quite small but show a modest increase in ACE2 levels with active smoking (32).…”
Section: Alteration In Ace2 Abundancementioning
confidence: 99%
“…Although a progressive decrease of the receptor expression with age has been described, 64 other authors reported a lower density of ACE2 in children compared to adult patients 65 . Most of the studies reported that the expression of ACE2 is enhanced in smokers and obese patients, 62 while data on the tissue levels of ACE2 in systemic and pulmonary disorders are not univocal 66–70 . However, the interest on ACE2 receptor in COVID‐19 is not limited to its role of binding site for SARS‐CoV‐2.…”
Section: Age‐related Role Of Extra‐immunological Factors In the Pathogenesis Of Covid‐19mentioning
confidence: 99%